Synthesis and Antimicrobial Activity of Novel Thiazolidinone and Azetidinone Derivatives - Kshirsagar, S.S.; Nimje, H.M.; Chaudhari, P.S.; Bayas, J.P.; Patel, E.K.; Karjikar, A.H.; Girme, P.D.; Oswal, R.J. (Asian Journal of Chemistry, 2011)
Reaction of 2,3-diketoquinoxaline in presence of phosphorus pentachloride and hydrazine hydrate gives 2-hydrazino-3-hydroxyquinoxalin (4) which on treatment with various aldehydes in appropriate solvent gives 2-p-anisyl-3-(3-hydroxy quinoxalin-2 yl-amino)-4-thiazolidinones (6) and 1-N-(3-hydroxy quinoxalin-2'yl-amino)-4-aryl-3-chloro-2-azetidinones (7). The structure of compounds 6a-6l and 7a-7l has been confirmed by IR and 1H NMR data. All these compounds were tested for their antimicrobial and antifungal activity against different microorganisms.